“Lexicographers of all countries, unite!” About the common semester of the European Master in Lexicography (EMLex) in Nancy - Blanck, Wiebke; Buchi, Éva (Lexicographica, 2019)
lexicography; European Master in Lexicography (EMLex)
Keywords: lexicography; European Master in Lexicography (EMLex)